REDEFINITION OF FEMALE STEREOTYPES PRESENTED IN TRIS PRIOR IN VERONICA ROTH’S NOVEL DIVERGENT - WARDHANI, KEN RESPATI PRIATIDITA CHANDRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Divergent, Female Stereotype, Feminism. The term of sex and gender are familiar in social life. Sex and gender which are attributed in a person are different each other. Sex is the organ adheres in human body since they born until grow up and it is natural. On the other hand, gender is the characterization which is constructed by social based on the sex. The concept of gender leads the different treatment and stereotypes between men and women. Redefinitions of female stereotype are found in literary works, which is found in Veronica Roth’s novel entitled Divergent. This novel tells about Tris Prior who redefinites female stereotypes.This research uses the feminist approach to analyze Tris’s characteristics in fighting for the opportunity to develop her potential in anotherfaction, suitable with her characteristics. Dring  her struggle, Tris shows that there is the redefinition of female stereotype in her characteristics.The research findings shows that Tris is portrayed as a smart, courageous, persevering, and determined woman who has the leadership skill. These traits have helped her survive in Dauntless. The next researchers are suggested to analyze more to reveal Tris Prior’s characters and motifs using psychological approach in order to reach a more comprehensive analysing on the novel.